The Evolution of E-Justice in European Credit Protection Procedures - Lidia DOMÍNGUEZ RUIZ (Revista Jurídica Portucalense, 2022)
In this paper, we want to leave proof of the evolution of online justice in European credit protection procedures. Specifically, in the European order for payment procedure and in the European small claims procedure. To do this, we will analyse the different European action plans on the matter, and we will see their impact on this type of procedure. This will allow us to delimit the progress of online justice in this area and to see future perspectives.